PENINGKATAN PROFESIONALITAS GURU MELALUI SUPERVISI AKADEMIK DI SMP NEGERI 3 PEUSANGAN KABUPATEN BIREUEN - Ainon Mardhiah; Yusrizal .; Nasir Usman (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2014)
Abstract: Academic supervision is strongly important to be conducted by the principal in order to improve the ability and professionalism of teachers. The purpose of this research is to find out the program of academic supervision, the implementation of academic supervision and the approach used in implementing academic supervision at State Junior High School (SMPN) 3 Peusangan of Bireuen Regency. The method employed within this research was qualitative approach. The data were collected through observation, interview, and documentation study. The subjects of this research were the principal and teachers ofSMPN 3 Peusangan, Bireuen. The results revealed that (1) the principal compiles the program of academic supervision through discussion with the vice principals and teachers; (2) the implementation of academic supervision conducted by the principal is regularly scheduled based on teachers’ invitation and also unscheduled without advance notification. The principal and vice principal of academic affairs share their duty in implementing academic supervision; (3) the technique of supervision performed by the principal is through visiting, observing and grouping classes. Yet, the supervision method used has not varied yet. It can be seen from the implementation of supervision including its process that the implementation of supervision by the principals of SMPN 3 Peusangan, Bireuen has not fully maximized yet. In order to follow up the results of academic supervision, the principal is expected to supervise, guide and assist the teachers such as encouraging them to take part in seminar and training through inviting skilled and competent speakers. Finally, the principal is also expected to provide the opportunity for the teachers to continue their study to the university.Keywords: Supervision and Teachers’ ProfessionalismAbstrak: Supervisi akademik sangat penting dilakukan oleh kepala sekolah dalam rangka meningkatkan kemampuan profesionalitas guru. Tujuan penelitian ini adalah untuk mengetahui program supervisi akademik, pelaksanaan supervisi akademik, dan teknik yang digunakan dalam pelaksanaan supervisi akademik di SMP Negeri 3 Peusangan Kabupaten Bireuen. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data: observasi, wawancara, dan studi dokumentasi. Subjek penelitian adalah kepala sekolah dan guru SMP Negeri 3 Peusangan Bireuen. Hasil penelitian menunjukkan bahwa: (1) Kepala SMP Negeri 3 Peusangan Bireuen menyusun program supervisi akademik secara musyawarah dengan melibatkan wakil kepala sekolah dan para guru , (2) Pelaksanaan supervisi akademik oleh kepala sekolah dilakukan secara terjadwal atau berdasarkan undangan guru dan tidak terjadwal atau tanpa pemberitahuan kepada para guru terlebih dahulu. Dalam melaksanakan supervisi akademik kepala sekolah juga membagi tugas supervisi dengan wakil kepala bidang akademik (3) Teknik supervisi yang digunakan kepala sekolah adalah kunjungan kelas, observasi kelas, dan teknik kelompok. Namun, teknik supervisi yang digunakan belum bervariasi. Dilihat dari pelaksanaan supervisi serta prosesnya, maka dapat dinyatakan bahwa pelaksanaan supervisi oleh kepala sekolah SMP Negeri 3 Peusangan Bireuen dikategorikan belum begitu maksimal. Untuk menindak lanjuti hasil supervisi akademik ditempuh dengan membimbing, mengarahkan, membantu para guru, mengikuti seminar, penataran dan mengundang narasumber yang kompeten. Disamping itu kepala sekolah juga memberikan kesempatan kepada para guru melanjutkan pendidikan ke perguruan tinggi.Kata Kunci: Supervisi dan Profesionalitas Guru.